The eﬀect of plyometric exercise on bone mineralisation and physical ﬁtness in adolescents - Syahrul, Syahrul; Rijal, Rijal; Hardianto, Yudi; Rabia, Rabia (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Plyometric exercise is the preferred type of exercise to promote bone health due to its role on providing high-im-pact loading of bone tissue. This study aimed to evaluate the eﬀect of plyometric training on bone mineralisation and physical ﬁtness between male and female adolescents.Methods. This study was a parallel 2-arm trial with 1:1 randomisation to the plyometric or control group. This study was conducted at SMA Negeri 21 Makassar, Indonesia, which included 18 second year of high school students actively engaging in physical activ-ity at least once a week. The plyometric training consisted of a warming-up period, plyometric session, and cooling-down period performed by participants in the plyometric group, three days/week for six months. The control group was informed to stay active during the study period. Bone mineralisation and physical ﬁtness were assessed at baseline and after the 6-month intervention.Results. A signiﬁcantly higher improvement of VO2 max was presented in the female plyometric group, compared to the control group (% improvement: 81.6 and 13.4 respectively; p < 0.001) over time. The plyometric group also experienced a signiﬁcant increase (+4.9 cm) in body height over time, while the control group only demonstrated a slight increase (+1.4 cm). Signiﬁcant increases in total dual femur BMD and trochanter BMC were observed in the male plyometric group.Conclusions. The increases in BMD and BMC were only observed in male adolescents following plyometric training. Meanwhile, improvement in VO2 max was more pronounced in female adolescents engaging with plyometric training.
Keywords: adolescent; body height; bone density; exercise; oxygen consumption